An Electrochemically Anodic Study of Anatase TiO2 Tuned through Carbon-Coating for High-performance Lithium-ion Battery. (10th May 2015) - Chen, Jun; Hou, Hongshuai; Yang, Yingchang; Song, Weixin; Zhang, Yan; Yang, Xuming; Lan, Qing; Ji, Xiaobo
Highlights: Carbon-coated anatase TiO2 nanoparticles were prepared via a novel and facile in-situ methodology. TiO2 /C nanocomposites exhibite high capacity and notable rate performances as anode in lithium-ion batteries. Such composite can offer great potential promise in large-scale energy storage applications. Abstract: A novel and facile in-situ methodology has been developed to prepare well carbon-coated anatase titanium dioxide (TiO2 ) nanoparticles. The hydrolysis of tetrabutyl titanate has been effectively controlled in a collosol of N-methyl-2-pyrrolidone dissolved with polyvinylidene fluoride. The as-resulted carbon-dispersed TiO2 nanoparticles distributed in ranges from 20 to 30 nm in diameter have been obtained with a carbon content of 11.7 wt%. This nanocomposite utilized as anode materials in lithium-ion battery can deliver a high reversible specific capacity of 218 mAh g −1 at the current density of 0.2 C (33.5 mA g −1 ), and still exhibit 100 mAh g −1 at 10 C (1.68 A g −1 ), illustrating notable high-rate performances for the potential application in fast charge/discharge batteries.